Changes in antimicrobial resistance and outcomes of health care-associated infections - BİLGİN, HÜSEYİN (SPRINGER, 2021)
To describe the change in the epidemiology of health care-associated infections (HAI), resistance and predictors of fatality we conducted a nationwide study in 24 hospitals between 2015 and 2018. The 30-day fatality rate was 22% in 2015 and increased to 25% in 2018. In BSI, a significant increasing trend was observed for Candida and Enterococcus. The highest rate of 30-day fatality was detected among the patients with pneumonia (32%). In pneumonia, Pseudomonas infections increased in 2018. Colistin resistance increased and significantly associated with 30-day fatality in Pseudomonas infections. Among S. aureus methicillin, resistance increased from 31 to 41%.
Keywords: Health care; associated infections; Blood stream infections; Colistin resistance